EFFECT OF VARIATIONS OF PHYSICOCHEMICAL PARAMETERS AMONG SELECTED FISH PONDS IN GOMBE STATE, NIGERIA - MUHAMMAD, KABIRU; ALIYU IDRIS K.B; SAIDU, HARUNA; MUHAMMED, ISHAKU; ABUBAKAR, ZAINAB A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
Fishing activities has been known to be the common sources of food and employment to the people leaving around riverine area. As such, increase in agricultural activities such as fertilizer application has led to the severe alteration of the chemistry nature of the water body thereby affecting the fishing activities. Analysis of the physicochemical parameters of some selected Ponds at Kwadon area of Yamaltu Deba LGA, Gombe State were conducted with the aim of determining the effect changes in physicochemical parameters on aquatic biota. Standard laboratory techniques were employed for the analysis of the parameters. Results of the study showed that, the average values of the temperature, pH, dissolve oxygen (DO), Biochemical oxygen demand (BOD), Total hardness, Conductivity and Total dissolve solid (TDS) were found to be at ranged of 27.4oC±0.56- 27.6oC±1.2, 6.68±0.1-7.62±0.30, 4.66±4.45-13.84±3.96mg/L, 1.69±1.13-7.7 7±2. 89 mg/L, 23.50±1.7-31.20±0.80 mg/L, 15.90±0.68- 22.10±0.78 mg/L, 139.70±3.90-247.40±1.5 S/cm, 66.90±12.28-113.90±75.86 mg/L. These values were found to be within the ranges recommended for good fish production, indicating the minimal effect of agricultural activities on the healthy state of the ponds. Hence suggesting good environmental conditions for fish survival and growth.